2020
DOI: 10.3389/fmed.2020.603303
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis in the Diagnosis of Primary Breast Cancer: Comparison of High-Resolution Dedicated Breast Positron Emission Tomography (dbPET) and Whole-Body PET/CT

Abstract: Objective: This retrospective study aimed to compare the ability to classify tumor characteristics of breast cancer (BC) of positron emission tomography (PET)-derived texture features between dedicated breast PET (dbPET) and whole-body PET/computed tomography (CT).Methods: Forty-four BCs scanned by both high-resolution ring-shaped dbPET and whole-body PET/CT were analyzed. The primary BC was extracted with a standardized uptake value (SUV) threshold segmentation method. On both dbPET and PET/CT images, 38 text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…32,33 parathyroid,34 breast,35,36 kidney,37 and prostate 38. Here, for the first time, we applied this engineering technology to the testis, confirming that US texture features could be useful in clinical practice to monitor testicular function during infertility work-up.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…32,33 parathyroid,34 breast,35,36 kidney,37 and prostate 38. Here, for the first time, we applied this engineering technology to the testis, confirming that US texture features could be useful in clinical practice to monitor testicular function during infertility work-up.…”
supporting
confidence: 61%
“…However, when all semen parameters have been considered together, multivariate and classification analyses confirmed the predictive ability of US texture to classify patients according to semen abnormalities, including sperm morphology. The radiomics ability to describe tissue structure and to predict tissue function has been recently confirmed in different contexts, such as thyroid, 32 , 33 parathyroid, 34 breast, 35 , 36 kidney, 37 and prostate. 38 Here, for the first time, we applied this engineering technology to the testis, confirming that US texture features could be useful in clinical practice to monitor testicular function during infertility work‐up.…”
Section: Discussionmentioning
confidence: 96%
“…This imaging modality provides a very high detection rate, thanks to its 1.5–2.0 mm spatial resolution [ 99 ]. In a few studies, textural features were extracted to make a direct comparison between dbPET and whole-body PET [ 57 , 58 , 59 ]. Satoh et al [ 57 ], in a retrospective study of 44 patients, compared the two tomographs in classifying tumor characteristics of BC, obtaining similar results for both dbPET and whole-body PET/CT.…”
Section: Resultsmentioning
confidence: 99%
“…In a few studies, textural features were extracted to make a direct comparison between dbPET and whole-body PET [ 57 , 58 , 59 ]. Satoh et al [ 57 ], in a retrospective study of 44 patients, compared the two tomographs in classifying tumor characteristics of BC, obtaining similar results for both dbPET and whole-body PET/CT. Conversely, Moscoso et al [ 59 ], demonstrated strong correlations between FDG dbPET-derived radiomic features and both immunohistochemistry and molecular subtypes of BC, stronger than those obtained by whole-body PET.…”
Section: Resultsmentioning
confidence: 99%
“…Spiral PC-BCT instead, is a truly three-dimensional breast imaging modality suitable for TA. To the best of our concerns, our study is the first investigating the potential of TA in spiral PC-BCT, though there have been investigations on cone-beam CT or positron emission tomography/CT in BC patients [ 18 , 37 ]. Due to its three-dimensional nature, spiral PC-BCT can provide around 3,500 images (including raw data images and high-resolution images), resulting into a systematically higher evaluation time.…”
Section: Discussionmentioning
confidence: 99%